PALOMARES ALARCÓN, Sheila (ed.) (2024). Agua y Patrimonio Cultural, Madrid: Dykinson, S.L., Instituto de Estudios Giennenses, Diputación de Jaén. ISBN: 978-84-1070-606-4 - Pablo Gumiel-Campos (E-RPH)
.